Does the City of Ends Correspond to a Classless Society?: A New Idea of Democracy in Sartre's Hope Now. Issue 1 (1st June 2019) - Russo, Maria
Abstract : In the Critique of Dialectical Reason and in many interviews, Sartre upheld the proletariat's attempts at emancipation in Western societies and their revolts in the developing world. In these texts, counter-violence is considered the only way to exercise concrete engagement, and a classless society is presented as the only possibility of reducing social inequalities. However, this radical point of view was not the only perspective he tried to develop. He also sought to elaborate an existentialist ethics, which does not correspond to the Marxist theory. This article aims to show that Sartre evoked Notebooks' ideas in his last interview, Hope Now, in which he envisaged a different typology of democracy and society. This article will examine this new and last direction of Sartre's political thought.